2019
DOI: 10.1038/s41598-019-43588-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Metamaterials Based on Self-assembled Titanium Dioxide Rolls with Embedded Gold Nanoparticles

Abstract: An experimental method for fabrication of a nanocomposite metamaterial based on a self-assembly of titanium dioxide microtubes with encapsulated gold nanoparticles (NPs) is proposed. The formation of microtubes is induced by laser irradiation in the presence of an external magnetic field. It is shown that the variation of the metal NP concentration leads to the increase of the optical absorption of the metamaterial. The possibility of using arrays of oriented microtubes as absorbing n-doped layers for solar ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We used pure titanium bulk crystals produced by LTd Ligamet (Moscow, Russia) as a target for laser ablation [ 14 , 15 ]. A titanium crystal was irradiated by nanosecond laser pulses from IR-source L-Designer made by Ateco (Moscow region, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…We used pure titanium bulk crystals produced by LTd Ligamet (Moscow, Russia) as a target for laser ablation [ 14 , 15 ]. A titanium crystal was irradiated by nanosecond laser pulses from IR-source L-Designer made by Ateco (Moscow region, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…Nanocomposite membranes that can manipulate heterogeneous surface potentials enhance rapid bone regeneration by enhancing RGD (Arg-Gly-Asp) peptide binding and stem cell mechanical sensing, providing an alternative strategy for constructing novel dental stem cell scaffolds to repair intact mature bone structures ( Li et al, 2020a ). In addition, some scientists found that titanium-coated gold nanoparticles enhanced the osteogenic differentiation of human adipose-derived stem cells by increasing the Wnt/β-catenin signaling pathway ( Kutrovskaya et al, 2019 ).…”
Section: Role Of Cell Optimization In Oral Diseasesmentioning
confidence: 99%
“…The perfect light absorption of photocatalysts modified by metamaterials is due to their spatial architecture, which can be fabricated through different methods such as the self-assembly of semiconductors with plasmonic nanoparticles. 153 6.2. Tunable Band Gap.…”
Section: Insights Of 1d/2d Photocatalysismentioning
confidence: 99%
“…The design and modification of spatially ordered metamaterials made of periodically modulated nanostructures (e.g., semiconductors and plasmonic nanoparticles) can result in 100% absorption of the irradiated light. The perfect light absorption of photocatalysts modified by metamaterials is due to their spatial architecture, which can be fabricated through different methods such as the self-assembly of semiconductors with plasmonic nanoparticles …”
Section: Strategies For Enhancing the Photocatalytic Performancementioning
confidence: 99%